Needs’ Conflicts of Teenagers as the Problem of Morality - Čiuladienė, Gražina (Acta Paedagogica Vilnensia, 2007)
The article seeks 1) to bring out peculiarities of adolescents’ conflicting action when their contradictors become classmates, teachers and parents, 2) to analyse the level of the frustration of teenagers needs’. The type of investigating adolescents’ conflicts is determined by needs’ conflict. It was defined in the article as conflict caused by classmates’, teachers’, parents’ behaviour, frustrating adolescents’ needs: 1) need for feeling grown-up, 2) need for empathy, 3) need for appreciation; 4) need for safety. Three types of conflicting teenagers’ behaviour is determined in the research: 1) aggressive treatment 2) egressive treatment 3) regressive treatment. The investigation was carried out with the 586 pupils aged from 12 to 16 years (7111-91h grades), learning in town, regional and country Lithuanian secondary schools. The link between adolescents’ conflicting action and frustration of adolescents’ needs is established. According to data analysis, the classmates’ behaviour, frustrating adolescents’ needs, most of all conditions the teenagers’ egressive classmates’ treatment. Dissatisfaction with teachers’ behaviour mostly influences adolescents’ egressive, self-aggressive and verbal aggressive treatment. The greatest influence on the adolescents’ conflicting action has the parents’ behaviour, frustrating adolescents ’needs. It has also been established that the teenagers’ need for empathy as well as the need of appreciation is frustrated mostly by teachers. According to data analysis there are 27 percent of pupils who often feel frustrated lacking the empathy and about 24 percent of pupils who often feel frustrated lacking the appreciation interacting with teachers. The need for feeling grown-up is mostly dissatisfied interacting with parents: about 22 percent of pupils often feel frustrated lacking appreciation of their independent decisions. The need for safety is mostly frustrated by classmates: about 12 percent of pupils lack the feeling of safety interacting with classmates.